Accessible tourism : an assessment of senior tourists on facilities at cultural and historical tourist attractions in Phuket based on the seven principles of universal design - Kanokros Khaonoul (Prince of Songkla University, 2019)
Thesis (M.B.A., Hospitality and Tourism Management (International Program))--Prince of Songkla University, 2018